Unveiling the mystery: a rare case of localized malignant pericardial mesothelioma—case report - Zhang, Yan; Pang, Mingjie (Frontiers in Oncology, 2024)
Abstract Primary malignant pericardial mesothelioma (PMPM) is a rare pericardial malignant tumor. Most manifestations of PMPM are localized or diffuse masses surrounding the heart. The prognosis of diffuse PMPM is poor due to the difficulty of surgical resection. Although the edge of localized PMPM is clear and can be easily resected, the diagnosis of this disease is difficult. Timely diagnosis and proper treatment are key to a good prognosis. Here, we report a patient with localized PMPM and describe the method for the diagnosis of this disease. Keywords 24 h pericardial effusion drainage, wax tissue, late gadolinium enhancement cardiac magnetic resonance